MegamergersMegamergers, by DavidsonKenneth M.. Cambridge, MA: Ballinger Publishing Company, 1985, 413 pp., $24.95, cloth. - Montgomery, Cynthia A. (Academy of Management Review, 1986)
The article presents a review of the book ?Megamergers,? by Kenneth M. Davidson.